Two new species of Plutomurus Yosii (Collembola: Tomoceridae) from the Caucasus and central Europe - Barjadze, Shalva; Parimuchová, Andrea; Raschmanová, Natália; Maghradze, Eter; Kováč, Ľubomír (Zootaxa, 2022)
Plutomurus kharagauliensis sp. nov. from Kozmani Cave, Kharagauli Municipality, Georgia, and P. ruseki sp. nov. from the surface and subterranean habitats in different regions of Slovakia are described, illustrated and differentiated from other morphologically similar congeners. Both species are unique by dorsal macrochaetotaxy of head and abdomen. An identification key to the species of the genus Plutomurus reported from the Western Palearctic is presented.